Analysis on the Risk and Supervision of P2P Online Financing Platforms in China - Song, Zhi-hong; Tian, Yu-xin; Lee, Dong-mei; Qin, Jin-xia (International Journal of Emerging Trends in Social Sciences, 2019)
Microcredit is a vital breakthrough to solve the financial problems of low-income groups and small and medium-sized enterprises, while traditional microfinance providers can only meet a small proportion of their capital needs. By using internet technology, P2P online financing extends the innovative development of microcredit with the aim of solving traditional micro-credit problems. This paper mainly explores the existing online financing operation model of P2P in China, and summarizes the relevant problems, such as low entry barriers for P2P online financing enterprises and lack of supervision, Lack of verification on the qualification of borrowers and poor management of the platform, imperfect information revealed or providing false information by platform, etc. Finally, the article put forward some suggestions concerning the healthy development for the P2P online financing platform, including the establishing entry audit system and strengthening the supervision of the P2P platform, strengthening the management of borrowers and improving the credit collection system, and strengthening the disclosure of information by platform.